Eva Canel y la preceptiva galdosiana - González Gallego, Daniel (Verba hispanica, 2020)
The present paper explores Eva Canels' literary production in relation to Galdós' lo real descarnado, taking as a reference point his acceptance speech at the Spanish Royal Academy in 1897. The similarities and differences between Canel and Galdós' modus scribendi are be analysed in a specific context: the colonial era and the Spanish crisis at the turn of the century. The analysis centres on the link between reality on the one hand,and representation on the other, which forms the basis for literary mimesis. This in turn enables us to understand the mechanisms used by Eva Canel to construct a historical account in line with her authorial strategies.
Keywords: 19 st.; Canel, Eva; hispanoameriška književnost; Latin American literature; realistic novel; realistični roman